Changing the meaning behind what we percieve as our 'community'. what it really means when we acknowledge that we are part of a society. - Kwok, Beryl Liwen. (2012)
There is a lack of attention and concern given to individuals who are unable to keep up with our fast-paced society. While Singaporeans are known for their generous monetary contributions to charities, there is an apparent disconnect between the general public and those who are unable to catch up with the society. This attitude has subsequently led to a slow but obvious degeneration of our community and our concept of a nation. This project aims to develop the notion of what we perceive as a community and to provoke a shared awareness of the political, social, cultural and technological contexts in Singapore.